The specifics of the development of the agricultural land market: the experience of Europe and the countries of Central Asia - I.O.; L.V.; Yu.V. (Економіка, управління та адміністрування)
Effective functioning of agricultural land markets is a prerequisite for the development of agriculture and rural areas as a whole. However, agricultural land markets remain weak and face many constraints in Eastern Europe and Central Asia. Applying a five-stage agricultural land market development conceptual framework, the paper assesses the current stage of land market development in Eastern Europe and Central Asia and discusses key constraints, including informality, lack of ownership, technical errors and transaction procedures. In most countries, agricultural structures are characterized by excessive land fragmentation and small average farm sizes. The necessity of a coordinated national land policy is argued. In addition, land management tools such as land consolidation and the land bank, apart from promoting the development of agriculture and rural areas, also contribute to the development of the land market. Despite numerous efforts since the start of the transition in 1990 by governments and donors in Eastern Europe and Central Asia, agricultural land markets in general are still weak, with numerous interrelated constraints preventing their development. The purpose of the study is to provide an overview of the level of development of agricultural land markets in the countries of Eastern Europe and Central Asia, to analyze and systematize the main limitations that prevent the further development of agricultural land and land markets. The other goal is to propose solutions to these problems, such as: land management tools, land consolidation and land banks. This will contribute to the development of agriculture and rural areas, as well as the development of the land market as a whole. The countries and territories analyzed in this article are Albania, Armenia, Azerbaijan, Belarus, Bosnia and Herzegovina, Georgia, Kazakhstan, Kosovo, the Kyrgyz Republic, the Republic of Moldova, Montenegro, North Macedonia, Serbia, Tajikistan, Turkey, Turkmenistan, Ukraine and Uzbekistan. The general experience of Eastern Europe and Central Asia regarding the specifics of the development of the agricultural land market should be taken into account in the field of land policy of Ukraine.